Parental presence improves pediatric MRI success without sedation: a prospective randomized study - Iwayama, Hideyuki; Hayata, Noriko; Takagi, Mizuki; Fukatsu, Ryohei; Kawahara, Kohei; Somiya, Hiroaki; Sada, Jun; Numoto, Shingo; Yamakawa, Kiyoshi; Miyamoto, Ryosuke; Mori, Hiromitsu; Muto, Taichiro; et al. (Frontiers in Pediatrics, 2025)
IntroductionMagnetic resonance imaging (MRI) requires children to remain still for extended periods, often necessitating sedation, which carries risks and raises costs. Non-pharmacologic strategies such as video goggles, evening scheduling, mock MRI training, and child life specialist-led preparation have been explored. The effectiveness of parental presence, especially in younger children, remains underexamined.MethodsThis prospective, single-center, randomized controlled trial included children aged 3–10 years referred for short stature evaluation. All were admitted for GH testing and underwent pituitary MRI if peak GH was ≤6.0 ng/ml. Participants were stratified by age (3–6 and 7–10 years) and randomized to parent present or absent groups using block randomization. MRI success was assessed in three steps: Step 1, completion of all sequences; Step 2, image quality (no, mild, or severe artifacts) evaluated blindly by two pediatricians; Step 3, final success defined as completion with no or mild artifacts. Exploratory variables included sibling number and crying during routine vaccinations.ResultsEighty children were enrolled, with 40 assigned to each group. Step 1: Completion rates were 30/40 (75.0%) in the parent present group and 22/40 (55.0%) in the parent absent group (P = 0.25). In children aged 3–6 years, completion was significantly higher in the parent present group (13/22, 59.1%) than in the parent absent group (4/22, 18.2%) (P = 0.012). Step 2: Among 52 who completed MRI, image quality was no/mild/severe artifact in 11/17/2 children (parent present) and 12/10/0 (parent absent) (P = 0.38). Step 3: Final success was achieved in 28/40 (70.0%) in the parent present group and 22/40 (55.0%) in the parent absent group (P = 0.25). In the 3–6-year subgroup, success was significantly higher in the parent present group (P = 0.012; OR = 6.50, 95% CI: 1.64–25.76). No difference was observed in the 7–10-year subgroup. Crying during vaccinations and sibling number were not associated with MRI success.DiscussionParental presence significantly improved non-sedated MRI success in children aged 3–6 years. Compared to other interventions, it is simple, safe, low-cost, and requires no specialized resources, supporting its use as a first-line strategy in younger children.